Severe orbital cellulitis secondary to chronic sinusitis: challenges in saving the eye - Diymitra K Ganasan; Mushawiahti Mustapha; Aida Zairani Mohd Zahidin (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Orbital cellulitis is a relatively common disease affecting predominantly the paediatric population. Most cases occur as a result of spread from the nearby sinuses. Other causes include penetrating trauma or extension from infected adjacent structures.If left untreated, this condition may result in devastating sequelae such as orbital apex syndrome, cavernous sinus thrombosis, meningitis, cranial nerve palsies, intracranial abscess formation and even death. A 47 year old immunocompetent Burmese lady presented with left eyelid swelling of 2 days duration associated with eye redness, blurring of vision and diplopia. Previously, there was history of right maxillary sinusitis and parapharyngeal abscess 9 months prior to presentation. On examination, she was afebrile with vision of 1/60 for the left eye with positiverelative afferent pupillary defect (RAPD). The eye was proptosed and swollen with restricted extraocular movements in all gazes. Conjunctiva was injected with chemosis and there was corneal epithelial bedewing. Otherwise anterior chamber was quiet and intraocular pressure was 51mmHg. Bilateral fundus examination was normal. Computed tomography (CT) scan of the orbit and paranasal sinus showed dense sinusitis and periosteal abscess at the lateral orbital wall.She was started on intravenous (IV) Cefuroxime and Metronidazole and underwent Functional Endoscopic Sinus Surgery (FESS) and orbital decompression. Intra-operatively there was pus and debris at the left anterior ethmoid, maxillary and sphenoid air sinuses and cultures revealed Klebsiella pneumoniae which was sensitive to Cefuroxime. Despite medical and surgical treatment, left orbital swelling only reduced minimally. However after starting intravenous Dexamethasone the swelling dramatically improved. She completed 10 days of intravenous Dexamethasone. Upon discharge, she was given oral Dexamethasone 2mg daily for 2 weeks and completed 2 weeks of oral Cefuroxime and Metronidazole. Intraocular pressure normalised and vision recovered to 6/9. A repeat CT orbit 3 weeks later showed resolving preseptal and periorbital collection.